PRODUKTIVITAS DAN RENDEMEN PEMBUATAN ANYAMAN PURUN (Lepironia articulata Domin) SERTA KONTRIBUSINYA TERHADAP PENDAPATAN DI DESA SUNGAI KALI KECAMATAN BARAMBAI KABUPATEN BARITO KUALA - Andrie Setiawan; Zainal Abidin; Diana Ulfah (Jurnal Sylva Scienteae, 2020)
The purpose of this study was to determine the magnitude of productivity, yield, and contribution of the purun woven craft industry in the form of mats and purun hats for the community in the Kali River village of Barambai sub-district, Barito Kuala district. The results of this study are (1) the average value of productivity of purul purun woven crafts is 0.466 pieces / hour, 3,207 pieces / day, 22 pieces / week, 87 pieces / month and 1039 pieces / year and the average value of productivity purun woven webbing 0.658 pieces / hour, 4,636 pieces / day, 32 pieces / week, 125 pieces / month and 1502 pieces / year. (2) The magnitude of the average yield of woven baskets is 75.096% and the average value of purun hat woven yield is 83.437%. (3) The amount of the average net income per year woven purun basket is Rp. 1,684,609.20 and the average value of annual net income of purun hat woven is Rp. 1,614,363.33, (4) The amount of the average contribution of purun baskets is 23.13% and the average value of purun woven contributions is 22.38% and the average value of the total contribution of purun woven is 40.99 %.Keywords: Purun; Productivity; Income; Contributions